Sifat Magnetik Material La0,6Ba0,4MnO3 dari LaMnO3 dan BaMnO3 Menggunakan Metode Kombinasi Sol-Gel dan Solid State - Saadah, Nelis; Jumaeri, Jumaeri; Putri, Witha Berlian; Munazat, Dicky; Kurniawan, Budhy (Indonesian Journal of Chemical Science, 2020)
Perovskite manganite is a manganese oxide-based magnetic material with the basic structure of AMnO3. Interactions between structures and electron transport of materials are studied of the substitution at position A. Perovskite material has interesting physical properties, such as magnetoresistance and magnetocaloric. The goal of research is to study the magnetic properties La0,6Ba0,4MnO3 from single-phase LaMnO3 and BaMnO3 compounds by combination sol-gel and solid state methods. Synthesis of LaMnO3 and BaMnO3 compounds using gel sol methods. The synthesis of La0,6Ba0,4MnO3 using solid state method, that is by mixing LaMnO3 and BaMnO3 powder mechanically and sintering at 1000Âº C for 24 hours. The characterization magnetic properties of La0,6Ba0,4MnO3 using Vibrating Sample Magnetometer indicate that the material is paramagnetic classified as soft-magnetic.